Separate origins of the left internal and external carotid arteries from the aortic arch and cervical internal carotid artery aneurysm in a patient with Noonan syndrome. (20th July 2016) - Tahir, Rizwan Ahmad; Asmaro, Karam; Pabaney, Aqueel; Kole, Max; Nypaver, Timothy; Marin, Horia
Abstract : Distinct origins of the external carotid artery and the internal carotid artery (ICA) from the aortic arch have been rarely described, and represent an aberrant development of the aortic arches during fetal life. This anatomical variation is usually discovered incidentally; infrequently, an aneurysm of the cervical ICA might accompany this rare configuration. We describe one such case in a patient with Noonan syndrome who presented with pulsatile neck mass. The diagnostic features and management of the aneurysm and a review of the literature are presented.